Iron Metabolism: An Under Investigated Driver of Renal Pathology in Lupus Nephritis - Wlazlo, Ewa; Mehrad, Borna; Morel, Laurence; Scindia, Yogesh (Frontiers in Medicine, 2021)
Nephritis is a common manifestation of systemic lupus erythematosus, a condition associated with inflammation and iron imbalance. Renal tubules are the work horse of the nephron. They contain a large number of mitochondria that require iron for oxidative phosphorylation, and a tight control of intracellular iron prevents excessive generation of reactive oxygen species. Iron supply to the kidney is dependent on systemic iron availability, which is regulated by the hepcidin-ferroportin axis. Most of the filtered plasma iron is reabsorbed in proximal tubules, a process that is controlled in part by iron regulatory proteins. This review summarizes tubulointerstitial injury in lupus nephritis and current understanding of how renal tubular cells regulate intracellular iron levels, highlighting the role of iron imbalance in the proximal tubules as a driver of tubulointerstitial injury in lupus nephritis. We propose a model based on the dynamic ability of iron to catalyze reactive oxygen species, which can lead to an accumulation of lipid hydroperoxides in proximal tubular epithelial cells. These iron-catalyzed oxidative species can also accentuate protein and autoantibody-induced inflammatory transcription factors leading to matrix, cytokine/chemokine production and immune cell infiltration. This could potentially explain the interplay between increased glomerular permeability and the ensuing tubular injury, tubulointerstitial inflammation and progression to renal failure in LN, and open new avenues of research to develop novel therapies targeting iron metabolism.